Synthesis of 4-Nitroisoxazoles via NO/NO2-Mediated Heterocyclization of Aryl-Substituted α,β-Unsaturated Ketones - Vasilenko, Dmitry A.; Sadovnikov, Kirill S.; Sedenkova, Kseniya N.; Kurova, Anastasiya V.; Grishin, Yuri K.; Kuznetsova, Tamara S.; Rybakov, Victor B.; Volkova, Yulia A.; Averina, Elena B. (Synthesis, 2020)
A straightforward approach for the synthesis of 4-nitroisoxazoles has been developed via heterocyclization of aryl/hetaryl-substituted α,β-unsaturated ketones upon treatment with tetranitromethane-triethylamine (TNM-TEA) complex or t-BuONO. This strategy features high efficiency and wide substrate tolerance under simple reaction conditions.
Keywords: 4-nitroisoxazoles; alkenes; ketones; heterocycles; ring closure; tert-butyl nitrite; heterocyclization; tetranitromethane